Risk Factors and Characteristics of Adverse Reactions Associated with the Use of Beta-Lactam Antibiotics in Older Patients - E. A. Sokova; V. V. Arkhipov; O. A. Demidova; I. A. Mazerkina; T. V. Alexandrova; M. V. Zhuravleva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
The frequency of adverse drug reactions (ADRs) in older patients is approximately 11.0%, according to scientific literature. Antibiotics are the third largest group (19.5%) of medicinal products in terms of ADR frequency in geriatric patients. Beta-lactam antibiotics are the empiric treatment of choice for older outpatients and inpatients with community-acquired pneumonia. The mortality in this group of patients accounts for 85% of the overall mortality from community-acquired pneumonia. The aim of the study was to analyse scientific data on risk factors and characteristics of adverse drug reactions associated with the use of beta-lactam antibiotics in older patients. Specificity of ADRs to beta-lactam antibiotics in this group of patients is due to age-related changes in pharmacokinetics and pharmacodynamics as well as polymorbidity and polypharmacy. The analysis of scientific literature demonstrated that there have not been so many pharmacoepidemiological studies in this group of patients, and their results have been inconsistent. The frequency, causes, and clinical manifestations of ADRs in geriatric patients are diverse and differ considerably from those in younger patients. Of the most widely used antibiotics, ceftriaxone and cefaclor exhibited a statistically lower risk of ADRs in older patients than in younger patients. At the same time, ceftriaxone was associated with a relatively higher frequency of serious ADRs in older patients as compared to younger patients, whereas the frequency of serious ADRs was lower with cefaclor. The likelihood of nephrotoxic, neurotoxic, and hepatotoxic ADRs associated with the use of beta-lactam antibiotics is becoming more and more obvious but it is still underestimated in clinical and geriatric practice. Safety monitoring, therapeutic drug monitoring with due consideration of ADR risk factors in older patients, and inclusion of older patients in clinical trials of antimicrobial drugs, would improve efficacy and safety of antibiotic treatment.